Pengaruh Profitabilitas, Likuiditas dan Leverage Terhadap Kebijakan Dividen Pada Sektor Infrastruktur - Agustinus Kismet Nugroho Jati (Fakultas Ekonomi Universitas Islam 45, 2022)
Dividend policy is a decision regarding the distribution of profits earned by the company, whether to be distributed to shareholders or to be retained in the form of retained earnings to finance investments in the future. This study aims to examine the effect of profitability, liquidity and leverage on dividend policy in infrastructure sector companies. Samples were taken as many as 14 companies. The method of determining the sample used in this research is purosive sampling. Data were analyzed using SPSS. The results showed that profitability had a significant positive effect on dividend policy. liquidity has no effect on dividend policy. leverage has no effect on dividend policy. This research suggests providing knowledge or education related to dividend policy.